Scientific knowledge and fourth-generation learning skills among university students in Saudi Arabia - Alsaadi, Ibrahim Abdu; Alshehry, Yazeed Mohameed; Saaty, Ahdab Abdalelah; Alhaj, Ferial Mahmoud (Journal of International Students, 2025)
The study assessed scientific knowledge and fourth-generation learning skills (4GLSs), including cognitive, information technology, creative thinking, and problem-solving skills, among University of Jeddah students in Saudi Arabia. We aimed to identify 4GLSs based on recent scientific research, construct scales to measure them, define the mechanism of their application and automation, and assess participants’ scientific knowledge and 4GLSs. After two pilot studies confirmed the validity and reliability of the measurement scales, a questionnaire survey was sent to all undergraduate students via official emails. Each skill was assessed via separate questionnaires distributed one week apart. The results revealed that 4GLSs increased with the student’s academic year. Differences were observed in creative thinking and problem-solving skills, with men scoring higher than women. Additionally, problem-solving skill levels were higher among students in the Faculty of Science than those in the Faculty of Arts.